1998
DOI: 10.1001/archinte.158.21.2329
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Heart Attack Symptoms in a Population Survey in the United States: The REACT Trial

Abstract: Knowledge of chest pain as an important heart attack symptom is high and relatively uniform; however, knowledge of the complex constellation of heart attack symptoms is deficient in the US population, especially in low socioeconomic and racial or ethnic minority groups. Efforts to reduce delay in seeking medical care among persons with heart attack symptoms should address these deficiencies in knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
103
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(123 citation statements)
references
References 36 publications
13
103
3
Order By: Relevance
“…Good knowledge was significantly correlated with a history of heart attack and a household income of $50,000 or more, which is consistent with results from the community-based telephone study by Goff et al (5). However, nearly 90% of individuals surveyed in that study were able to identify chest paint as a heart attack symptom (5), compared with 82% in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Good knowledge was significantly correlated with a history of heart attack and a household income of $50,000 or more, which is consistent with results from the community-based telephone study by Goff et al (5). However, nearly 90% of individuals surveyed in that study were able to identify chest paint as a heart attack symptom (5), compared with 82% in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…-based, open-ended telephone survey studies in the United States and Australia (5)(6)(7)(8)(9) have reported that awareness of all heart attack and stroke symptoms is low among the general public. Individuals categorized as being at higher risk for coronary artery disease have also been shown to exhibit poor knowledge of its risk factors (10,11).…”
Section: Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…Research clearly establishes the saliency of the role of uncertainty in clinical decision-making. Patients seek help, present symptoms, and respond to recommendations differently (Bursztajn, 1990;Goff et al, 1998). How people experience and report pain, for example, varies greatly and systematically with patient characteristics (Bonham, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…According to the Rapid Early Action for Coronary Treatment Trial, although knowledge of chest pain as an important heart attack symptom is relatively high in the US, there are racial and gender variations in identifying correct symptoms and signs of heart disease. 33 National efforts are needed to increase the proportion of the general public who recognize signs and symptoms of a heart attack and who are willing to participate in the "chain of survival," which includes dialing 911, attempting cardiac resuscitation, and using automated external defibrillators until emergency personnel arrive. 34 Finally, the primary prevention of coronary heart disease should remain a major focus of public health.…”
Section: Zheng Et Al Sudden Cardiac Death In Adults In the Us 2161mentioning
confidence: 99%